Analysis of the Defects Causes in Rolled Brass Sheet - Kuśmierczak, Sylvia; Náprstková, Nataša; Kuba, Michal (Manufacturing Technology Journal, 2014)
The aim of this paper is to identify the causes of defects in rolled brass sheets which appear in the final stage of the blank production. These defects cause the increase in the production cost of the blank, which is undesirable. The analysis methods were used, such as spectroscopic chemical analysis, microstructural analysis using light and electron microscopy and the application of selected mechanical tests. Based on the analysis results, the analysis and cause determining and type of qualification occurring defects was realized.
Keywords: defect; brass; analysis; microstructure; REM